On Quotient \(π\)-images of locally separable Metric Spaces - Van Dung, Nyguyen (Scientia Series A: Mathematical Sciences, 2025)
We prove that a space is quotient \(π\)-image of a locally separable metric space if and only if it has a \(π-\) and double \(cs*-\)cover. We also investigate quotient \(π-s-\) images of locally separable metric spaces.
Keywords: \(π\)-cover; double cs¨*-cover; \(π\)-mapping; \(s\)-mapping; quotient mapping; subsequence-covering mapping; sequentially-quotient mapping.